Decision Making and Policy Analysis in Transportation Planning (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The ongoing evolution in transportation planning necessitates a multifaceted approach to policy design and decision-making, incorporating technological advancements and changing societal needs. This Special Issue of Systems on "Decision Making and Policy Analysis in Transportation Planning" showcases pioneering research that addresses the critical elements of transportation planning, policy analysis, and system management. Each paper addresses critical aspects of transportation planning and policy analysis, offering new insights and solutions to contemporary transportation challenges. We hope that the insights presented in these papers will inspire further research and inform policy development, ultimately contributing to the creation of more sustainable, efficient, and equitable transportation systems.